COMMUNITY DEVELOPMENT BASED ONIBNU KHALDUN THOUGHT, SEBUAH INTERPRETASI PROGRAM PEMBERDAYAAN UMKM DI BANK ZAKAT EL-ZAWA - Hamdi, Muhammad Nurul; Nurjanah, Evi; Handayani, Latifah Safitri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
The aim of this research is to explain empowering small and medium enterprises model wich is interpreted from community development based on Ibnu Khaldun thought that reserved as the solution from el-Zawa’s technical constraints. The concept of development of those societies three lays of the basic principal, that are: individual, ashabiyah dan ijtima’ al-insan.This concept used in order to improving the quality and comprehensive and sustainable benefit. El-Zawa are the institutions established by Maulana Malik Ibrahim Islamic State University of Malang in order to collecting and managing funds of zakat, infaq, shadaqah, and waqf then spend that in societies economy empowering program. Qualitative research useful for a direct view of reality of field and collected information on power, potential and obstacle faced. The technique of using methode of Miles with three phases: data reduction, data display and drawing conclusions or verification. With the existence of this system, el-Zawa role in societies economy development will increase and able to solve the problems and having a very potential sector and significant in the Indonesian economy.